Illness perceptions in cancer survivors: what is the role of information provision?. Issue 3 (6th February 2012) - Husson, Olga; Thong, Melissa S. Y.; Mols, Floortje; Oerlemans, Simone; Kaptein, Adrian A.; van de, Lonneke V.
Abstract Background The aim of this study was to provide insight into the relationship between information provision and illness perceptions among cancer survivors. Methods All individuals diagnosed with lymphoma, multiple myeloma, endometrial or colorectal cancer between 1998 and 2008, as registered in the Eindhoven Cancer Registry, were eligible for participation. In total, 4446 survivors received a questionnaire including the EORTC‐QLQ‐INFO25 and the Brief Illness Perception Questionnaire; 69% responded (n = 3080). Results Lymphoma and multiple myeloma patients were most satisfied with the information they received, and they perceived to having received more information about their treatment and other services (after care) compared with colorectal and endometrial cancer survivors (p < 0.05). Multiple myeloma patients reported the highest scores (conceptualized their illness as very serious) on the illness perception scales. The perceived receipt of more disease‐specific information was associated with more personal and treatment control and a better understanding of the illness, whereas the perceived receipt of more information about other services was associated with more negative consequences of the illness on the patients' life, longer perceived duration of illness, less treatment control, more symptoms attributable to the illness, less understanding of, and stronger emotional reaction to the illness (p < 0.05). Satisfaction with the received information was associated with better illness perception on all subscales, except for personal control (p < 0.05). Conclusion Improving the patients' illness perceptions by tailoring the information provision to the needs of patients may help patients to get a more coherent understanding of their illness and will possibly lead to a better health‐related quality of life. Copyright © 2012 John Wiley & Sons, Ltd.